2006
DOI: 10.1021/la0613934
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Light Scattering, Interfacial Properties, and Conformational Analysis of Biodegradable Quarternary Ammonium Surfactants

Abstract: Aggregation properties of biodegradable ammonium surfactants containing amide and ester groups in the bulk and at the air-water interface were investigated as a function of surfactant tail length m using dynamic light scattering and surface tension experimental methods. The results indicate that surfactants containing an ester group in the structure display higher aggregation ability in the volume and form more densely packed layer of molecules at the air-water interface than those with an amide group. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Polymethylene spacer d2e containing two ester groups is even more flexible as results from the area per surfactant molecule curve lying below both area curves for surfactant molecules with the spacers containing amide groups. This generally corresponds with our previous experimental findings supported by the computer model of surfactant molecules containing ester and amide group that the spacer with the ester group is somewhat shorter and more conformationally flexible than that with the amide group which results in denser packing of surfactant molecules at the air-water interface [15].…”
Section: Comparison Of the Area Per Surfactant Molecule Values For Gesupporting
confidence: 91%
See 3 more Smart Citations
“…Polymethylene spacer d2e containing two ester groups is even more flexible as results from the area per surfactant molecule curve lying below both area curves for surfactant molecules with the spacers containing amide groups. This generally corresponds with our previous experimental findings supported by the computer model of surfactant molecules containing ester and amide group that the spacer with the ester group is somewhat shorter and more conformationally flexible than that with the amide group which results in denser packing of surfactant molecules at the air-water interface [15].…”
Section: Comparison Of the Area Per Surfactant Molecule Values For Gesupporting
confidence: 91%
“…In our previous study [15], we have found that the biodegradable ester group in a surfactant molecule structure is more flexible than an amide group. This results in a smaller area per surfactant molecule values at the air-water interface as well as corresponds with a shorter chain length calculated from the respective computer model of the surfactant molecule.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, the development of surfactants with an improved biodegradability and recyclability using renewable resources by an environmentally benign process is now needed with respect to the establishment of a green and sustainable chemistry. Biodegradable and cleavable surfactants, such as amino acid-based, sugar-based and ester containing surfactants, have so far been synthesized [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%